Improving Science Learning Outcomes Through The Project Based Learning (PBL) Model For Class V Students Of MI Ma'arif Klangon Kec. Kalibawang - Winarniyati, Winarniyati (Journal of Social Science and Economics, 2023)
The learning model that can be used in science learning in elementary schools as an alternative learning improvement in an effort to increase science learning outcomes for class V students at MI Ma'arif Klangon Kalibawang Kulon Progo Regency for the 2022/2023 academic year is the Project based Learning (PBL) learning model. This Project Based Learning (PBL) learning model prioritizes student activity and provides opportunities for students to develop their potential and improve student learning outcomes to the maximum. This research uses a type of classroom action research, where this type of research is a social study with the aim of improving the quality of learning actions so that it can improve the learning outcomes of Class V students in the odd semester of MI Ma'arif Klangon Kalibawang, Kulon Progo Regency, 2022/2023 academic year regarding the nature of -the nature of light. The results achieved in the first cycle were sufficient qualifications (C) or the majority of students did not understand the material given by the teacher so that the learning results were sufficient, in the second cycle the results achieved were Very High qualifications (ST) or all students had understood the material provided. This can be achieved because intensive guidance is continuously provided in the learning process.